2010
DOI: 10.1111/j.1365-2567.2009.03228.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of humoral and cellular immunity with an anti‐glucocorticoid‐induced tumour necrosis factor receptor monoclonal antibody

Abstract: Summary Adjuvants, including antibodies to tumour necrosis factor receptor superfamily members, augment immune responses. One member of this family, glucocorticoid‐induced tumour necrosis factor receptor (GITR), is expressed at low levels on naive/resting T cells, B cells and macrophages, but at higher levels on T regulatory cells. The aim of this study was to determine the ability of a rat anti‐mouse GITR monoclonal antibody, 2F8, to stimulate murine humoral and cellular immunity in a prime boost model with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 79 publications
(193 reference statements)
3
22
0
Order By: Relevance
“…33,43 We found that mMT mice, which lack mature B cells, were protected from anaphylaxis caused by DTA-1 ( Figure 3E) We observed that neutralizing IL-4 considerably reduced anaphylaxis severity ( Figure 3F). …”
Section: Anaphylaxis Is Caused By Repetitive Dosing Of Antibodies Tarmentioning
confidence: 70%
See 1 more Smart Citation
“…33,43 We found that mMT mice, which lack mature B cells, were protected from anaphylaxis caused by DTA-1 ( Figure 3E) We observed that neutralizing IL-4 considerably reduced anaphylaxis severity ( Figure 3F). …”
Section: Anaphylaxis Is Caused By Repetitive Dosing Of Antibodies Tarmentioning
confidence: 70%
“…Although GITR is expressed at much lower levels on B cells than on CD4 1 T cells (supplemental Figure 6), we also examined whether B cells were required for DTA-1-induced anaphylaxis, because GITR agonist antibodies have recently been shown to have potent humoral adjuvant effects. 33,43 We found that mMT mice, which lack mature B cells, were protected from anaphylaxis caused by DTA-1 ( Figure 3E). Because CD4 We observed that neutralizing IL-4 considerably reduced anaphylaxis severity ( Figure 3F).…”
mentioning
confidence: 89%
“…The potentiation of effector T cells is due to three mechanisms: costimulation of CD4 + and CD8 + T cells, resistance of effectors to Treg regulatory activity, and inhibition of Treg activity. These effects were obtained by using mAbs against GITR (DTA-1 and 2F8) [90,91].…”
Section: In Vivo Expansion Of Gitr + Tregs: a Potential Approachmentioning
confidence: 99%
“…Cross-linking of GITR using agonistic anti-GITR mAb (DTA-1) generally enhances immune responses in animal models involving viral infection, tumors, and autoimmune disease (6)(7)(8)(9)(10)(11)(12). GITR is an excellent adjuvant for humoral and cellular responses using agonistic mAb (13). Because the functions of mAbs are controlled by their Fc regions, anti-GITR mAb DTA-1 (rat IgG2b) essentially requires activating FcgR, but not inhibitory FcgRIIB, to suppress tumor growth and to eliminate intratumoral Treg cells in vivo (14).…”
mentioning
confidence: 99%